(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Siddha, a traditional system of medicine, leverages the therapeutic potential of herbs and natural substances to promote holistic health. In Siddha medicine, Maantham is categorised under Aga Karana Noigal, encompassing 21 types, including Por Maantham. The signs and symptoms of Por Maanthan are correlated with acute diarrhoeal disease. Poduthalaiyathy Kudineer, a classical Siddha polyherbal formulation, is traditionally used to treat Por Maantham, a condition akin to acute diarrhoeal disease. This comprehensive review aims to explore the therapeutic potential of Poduthalaiyathy Kudineer in managing Por maantham (acute diarrhoeal disease). Diarrhoea in children is a common and significant health issue worldwide, particularly in developing countries. It can lead to dehydration, electrolyte imbalance, malnutrition, and even death if left untreated or poorly managed. Children under the age of five are most vulnerable to diarrhoeal diseases due to their developing immune systems and increased exposure to pathogens. Effective management and prevention strategies are crucial to reducing the morbidity and mortality associated with diarrhoeal diseases in children. A thorough examination of traditional Siddha texts and contemporary scientific literature was conducted to elucidate the formulation’s composition, mechanism of action and efficacy. The review highlights the synergistic potential of Poduthalaiytahy kudineer’s multi-herbal components, which may contribute to its efficacy in managing acute diarrhoeal disease.